TERAPI REALITAS UNTUK MENANGANI TRAUMA (POST TRAUMATIC STRESS DISORDER) PADA KORBAN BULLYING DI BALAI PERLINDUNGAN DAN REHABILITASI SOSIAL WANITA YOGYAKARTA - Nur Hamid Ashofa (UIN Sunan Kalijaga Yogyakarta, 2019)
ABSTRACTBullying (violence) has a very negative impact on victims both physically and psychologically. Not all victims of bullying dare to share the problems they are experiencing with others, even though this is very disturbing to the psychic or emotional level of the client. The minimal level of awareness of the surrounding environment is also the reason for the lack of handling victims of bullying. When not getting the right treatment it will be very detrimental to the victims in the future, especially when victims of bullying are underage children. The impact that will be caused is trauma.In this study we will discuss how reality therapy is used to deal with trauma for victims of bullying in the women's social protection and rehabilitation center (BPRSW). This study will also use several other therapies including religious therapy. Because in practice if you only use one theory or only use one theory, it is not very effective to help deal with the trauma experienced by victims of bullying.The choice of subject here is with the approval of the hall, psychologist, and also confirmation to the LS (victim). The data obtained by researchers is derived from the results of interviews with the parties, psychologists, and also victims. From the results of interviews and also conducting observations in the field directly, reality therapy is believed to be used to deal with trauma to victims of bullying even though it requires several other therapies in its application and also requires a short time and more intensive counseling with victims. Keyword: Bullying, Reality Therapy.